2017
DOI: 10.2147/ott.s150456
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy induces ovarian cancer cell repopulation through the caspase 3-mediated arachidonic acid metabolic pathway

Abstract: Recurrence is one of the major causes of high mortality in ovarian cancer. However, the mechanism of ovarian cancer recurrence after chemotherapy has not been fully understood. In the present study, we investigated the effect of chemotherapy-induced tumor microenvironment on the proliferation of SKOV3 cells. We have shown that SKOV3 cells repopulated faster in the culture medium from apoptotic SKOV3 ovarian cancer cells after 24 h of etoposide phosphate (VP-16) treatment. We found that during apoptosis, cleave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…It has been shown that PGE 2 released from dying cells is captured by its membrane prostaglandin E2 receptor (EP2), a G‐protein‐coupled receptor of 53 kDa, which activates a series of cellular pathways involved in cell proliferation (Liou et al , ; Galluzzi, Kepp, & Kroemer, ). Other authors have further shown that PGE 2 is a potent stimulator not only of cell proliferation, but also of cell motility, invasion and angiogenesis (Cui et al , ) and is able to favour the formation of in vitro spheres and cell division of CSCs (Chan, ). The signalling cascade of caspase 3 mediated by AA and PGE 2 also activates the Wnt‐β‐catenin pathway, a proto‐oncogenic signalling cascade that is involved in the regulation of numerous intracellular processes, including proliferation (Goessling et al , ; Galluzzi et al , ; Cheng et al , ).…”
Section: Tumour Repopulationmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown that PGE 2 released from dying cells is captured by its membrane prostaglandin E2 receptor (EP2), a G‐protein‐coupled receptor of 53 kDa, which activates a series of cellular pathways involved in cell proliferation (Liou et al , ; Galluzzi, Kepp, & Kroemer, ). Other authors have further shown that PGE 2 is a potent stimulator not only of cell proliferation, but also of cell motility, invasion and angiogenesis (Cui et al , ) and is able to favour the formation of in vitro spheres and cell division of CSCs (Chan, ). The signalling cascade of caspase 3 mediated by AA and PGE 2 also activates the Wnt‐β‐catenin pathway, a proto‐oncogenic signalling cascade that is involved in the regulation of numerous intracellular processes, including proliferation (Goessling et al , ; Galluzzi et al , ; Cheng et al , ).…”
Section: Tumour Repopulationmentioning
confidence: 98%
“…AA and PGE 2 are bioactive lipids that elicit a wide range of biological effects associated with inflammation and cancer. In addition, they are potent growth promoters and stimulate proliferation and CSC growth (Lauber et al , ; Kurtova et al , ; Cui et al , ). It has been shown that PGE 2 released from dying cells is captured by its membrane prostaglandin E2 receptor (EP2), a G‐protein‐coupled receptor of 53 kDa, which activates a series of cellular pathways involved in cell proliferation (Liou et al , ; Galluzzi, Kepp, & Kroemer, ).…”
Section: Tumour Repopulationmentioning
confidence: 99%
“…In addition, a second-generation inhibitor VS-6063 (also known as defactinib or PF-04554878) of FAK/PYK2 has been used for phase I trial in Japanese patients with advanced solid tumors [ 89 ]. In ovarian cancer cells, administration of etoposide phosphate (VP-16) could promote SKOV3 cell apoptosis, but VP-16-induced repopulation effects were partially reversed by the FAK inhibitor PF562271 [ 90 ]. A recent study reported that two small molecule inhibitors PF-573228 and PF-431396, dual specificity inhibitors of FAK and PYK2, as well as another small molecule inhibitor VS-6063 (specifically inhibits FAK but not PYK2), could inhibit cancer cell growth and anchorage-independent colony formation and induce apoptosis and cell cycle arrest [ 91 ].…”
Section: Pyk2 and Cancersmentioning
confidence: 99%
“…Chemotherapy or irradiation stimulates the release of tumor-promoting lipid mediators, including prostaglandins, platelet-activating factor, sphingosine-1-phosphate (S1P), ceramide-1-phosphate (C1P), and lysophosphatidic acid into the tumor microenvironment (5,19,22,23). Chemotherapy has been recently reported to stimulate the proliferation of ovarian cancer cells through a caspase-3-mediated arachidonic acid pathway (24). Moreover, in vitro studies suggest…”
mentioning
confidence: 99%